CARE AND ACCESS IN EARLY HINDU BIOETHICS - Alla, Stanislaus (Asian Horizons, 2011)
Presently, both ‘boom’ and ‘denial’ largely characterize the health care services available in India. The April 12, 2010 issue of India Today in its cover story “The Healthcare Boom” reports on the phenomenal growth the nation experiences in this sector. Its affluent and middle classes can now afford to choose from a set of world class options available at a call away. However, the statistics alarm: “The private sector, up from Rs 85, 500 crore in 2006 to Rs 1, 48,050 crore now, accounts for 80 percent of the market – highest in the world. It also controls 60 percent of the 15, 393 hospitals in India…”1 At the same time, millions in India, both the rural and urban poor, are denied access to basic health care services. With the exception of a few, the underfunded, corrupt and inefficient hospitals in public sector consistently fail the people entrusted to their care. Lifestyle diseases have been rapidly spreading, affecting more poor people than ever in the past, while India still battles to eradicate the many contagious diseases.